2022
DOI: 10.3390/pathogens11121464
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii and Neospora caninum Antibodies in Dogs and Cats from Egypt and Risk Factor Analysis

Abstract: Background: Toxoplasma gondii and Neospora caninum are major protozoan parasites of worldwide distribution and significance in veterinary medicine and, for T. gondii, in public health. Cats and dogs, as final hosts for T. gondii and N. caninum, respectively, have a key function in environmental contamination with oocysts and, thus, in parasite transmission. Very little is known about the prevalence of T. gondii infections in dogs and cats in Egypt, and even less about the prevalence of N. caninum in the same h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Neospora caninum infection in Egyptian animals is underestimated, with a few seroprevalence reports in cattle, buffaloes, sheep, goats, camels, dogs, and cats, as well as limited information on clinical neosporosis. In our previous reports using the same ELISA as in the current study, we demonstrated seroprevalence rates for N. caninum of 3.9% in camels [44], 15.5% and 5% in sheep and goats, respectively [45], 5.8% in dogs, 3.4% in cats [49], and 24.6% in cattle [50]. Nonetheless, serum samples from aborted cows revealed N. caninum infections in addition to Coxiella burnetii [51] or Bovine Viral Diarrhoea Virus [52].…”
Section: Discussionsupporting
confidence: 80%
“…Neospora caninum infection in Egyptian animals is underestimated, with a few seroprevalence reports in cattle, buffaloes, sheep, goats, camels, dogs, and cats, as well as limited information on clinical neosporosis. In our previous reports using the same ELISA as in the current study, we demonstrated seroprevalence rates for N. caninum of 3.9% in camels [44], 15.5% and 5% in sheep and goats, respectively [45], 5.8% in dogs, 3.4% in cats [49], and 24.6% in cattle [50]. Nonetheless, serum samples from aborted cows revealed N. caninum infections in addition to Coxiella burnetii [51] or Bovine Viral Diarrhoea Virus [52].…”
Section: Discussionsupporting
confidence: 80%
“…However, neosporosis is often missed in diagnosing neurological disorders and myopathies in dogs and cats. The serological studies regarding N. caninum in domestic animals usually focus on dogs [ 6 13 ]. Several studies were conducted to determine the seroprevalence of N. caninum in domestic cats worldwide [ 13 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The serological studies regarding N. caninum in domestic animals usually focus on dogs [ 6 13 ]. Several studies were conducted to determine the seroprevalence of N. caninum in domestic cats worldwide [ 13 – 16 ]. Data on N. caninum seroprevalence in rabbits are scarce, although few reports indicate the presence of antibodies against N. caninum in rabbit sera [ 12 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the percentage of neutered cats, as well as those that live outdoors, are necessary data to evaluate population control, their environmental impact, and the dynamics of zoonoses and other diseases in whose cycle they are involved. Cats and dogs that live outdoors, with or without guardians, experience greater health risks than their indoor-living counterparts, and the overpopulation of free-roaming animals can result in other challenges, including traffic accidents, bite injuries, predation, and competition with wildlife [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The decision to allow cats access to the outdoors has not been found to be associated with their age, health status, or onychectomy status.…”
Section: Introductionmentioning
confidence: 99%